2016
DOI: 10.1681/asn.2014101035
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin as a Major Component of Renal Antibacterial Defenses against Uropathogenic Escherichia coli

Abstract: The iron-regulatory peptide hepcidin exhibits antimicrobial activity. Having previously shown hepcidin expression in the kidney, we addressed its role in urinary tract infection (UTI), which remains largely unknown. Experimental UTI was induced in wild-type (WT) and hepcidin-knockout (Hepc2/2) mice using the uropathogenic Escherichia coli CFT073 strain. Compared with infected WT mice, infected Hepc2/2 mice showed a dramatic increase in renal bacterial load. Moreover, bacterial invasion was significantly dampen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 54 publications
2
43
1
Order By: Relevance
“…Proximal tubules virtually do not synthesize hepcidin 15 but reabsorb filtered circulating hepcidin, whereas the distal tubules can synthesize hepcidin 14,15 but did not show uptake of the administered hhep25 in our studies. Interestingly, we observed that hhep25 injection in hemoglobin-treated mice led to a dramatic increase in renal Hamp1 mRNA expression and hepcidin immunostaining in the distal tubules.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Proximal tubules virtually do not synthesize hepcidin 15 but reabsorb filtered circulating hepcidin, whereas the distal tubules can synthesize hepcidin 14,15 but did not show uptake of the administered hhep25 in our studies. Interestingly, we observed that hhep25 injection in hemoglobin-treated mice led to a dramatic increase in renal Hamp1 mRNA expression and hepcidin immunostaining in the distal tubules.…”
Section: Discussioncontrasting
confidence: 65%
“…1 Hepcidin has been shown to be synthesized in the mouse kidney, specifically in the distal nephron segment. 14,15 However, it is unclear whether this locally synthesized hepcidin is excreted in the urine. Other than uncertainties concerning the origin of urinary hepcidin during CABG, gaps exist in our common knowledge on renal hepcidin handling.…”
mentioning
confidence: 99%
“…Hepcidin synthesis is also induced by inflammatory signals (such as IL‐6), and has a major role in the anemia associated with inflammation (Ganz, ). Although the liver is the major source of circulating hepcidin, the peptide is expressed (albeit to a lesser extent) by other organs (Coimbra, Catarino, & Santos‐Silva, ; Houamel et al, ; Qian et al, ; Wu et al, ). Interestingly, local hepcidin levels in brain cells (including neurons, astrocytes, and microglia) are extremely low under steady‐state conditions but rise dramatically under pathological inflammatory conditions (Urrutia et al, ; Simpson et al, )‐ suggesting that hepcidin is a causal factor in brain iron retention in the context of neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%
“…According to Kulaksiz et al, renal hepcidin is mostly located in the epithelial cells of the cortical thick ascending limb of nephron tubules and in the connecting tubules [34]. Local renal hepcidin produced by these cells is most likely secreted in the luminal surface of the epithelium [21,34,35], though other authors suggest that the local hepcidin could be secreted in bloodstream via basal membrane [36]. Veuthey et al have suggested that prohepcidin is produced by proximal tubule, though it has to be mentioned that authors of this study did not measure mRNA expression, but rather immunohistochemical expression of this peptide, which could mean that the presence of the peptide inside proximal tubular cells is due to absorption from the blood filtrate which contains the systemic form of the peptide [36].…”
Section: Renal Hepcidin Expression and Regulationmentioning
confidence: 99%
“…Finally, studies show that hepcidin might affect renal iron metabolism independently from FPN [21,37,42]. On the other hand, similarly to liver hepcidin, renal hepcidin could be induced through BMP6/SMAD pathway [35]. It is interesting to notice that the knockout of renal BMP6 is related to progressive renal damage due to a significant increase of iron load and oxidative stress [46].…”
Section: Renal Hepcidin Expression and Regulationmentioning
confidence: 99%